Targeting mTOR and AREG with Everolimus, Sunitinib and Sorafenib in HPV-positive and -negative SCC - Aderhold, Marc Christoph; Lammert, Anne; Umbreit, Claudia; Birk, Richard; Weiß, Christel; Sommer, Ulrich; Hörmann, Karl; Schultz, Johannes D. (Anticancer research, 2015)
Background/Aim: Head and neck squamous cell carcinoma (HNSCC) is an aggressive epithelial malignancy. It is the most common neoplasm appearing in the upper aerodigestive tract and the sixth most common cancer worldwide. The five-year survival rate remains poor despite advances in surgery, radiation and chemotherapy. Furthermore, the incidence of human papillomavirus (HPV)-associated oropharyngeal cancer is rising. Thus, innovative therapy approaches are imperative in order to improve the situation. Everolimus, an inhibitor of the mammalian target of rapamycin (mTOR) and sorafenib and sunitinib, multityrosine kinase inhibitors, have been notably effective in the therapy of different tumor entities. The modest side-effects and oral application of the drugs might improve patient compliance. Expression levels of mTOR and Amphiregulin (AREG) in p16-positive and -negative SCC (squamous cell carcinoma) and the effect of everolimus, sorafenib or sunitinib on the expression levels of these target proteins were assessed. As far as we are aware of, this is one of the first in vitro studies to evaluate the effect of these small-molecule drugs with regard to the p16 status of SCC cells. Materials and Methods: p16-negative HNSCC 11A and 14C cells and p16-positive CERV196 cells were exposed to different concentrations of everolimus, sorafenib and sunitinib for 2-8 days. Expression levels of mTOR and AREG were determined by enzyme-linked immunosorbent assay (ELISA) and compared against a chemonaïve control. Results: AREG and mTOR were expressed in all tested cell lines. CERV196 displayed a remarkable increase of mTOR expression compared to p16-negative HNSCC. On the contrary, AREG levels were reduced by 50% in CERV196. Everolimus, sorafenib and sunitinib significantly reduced mTOR expres sion. Everolimus significantly decreased AREG expression independently of the HPV status. Sunitinib and sorafenib increased AREG expression in HNSCC 11A and 14C but not in CERV196. Conclusion: The applied drugs showed remarkable suppression of mTOR expression, which might delay tumor progression. Interestingly, sorafenib and sunitinib increased AREG in HNSCC 11A and 14C, which could be a possible evasive mechanism following incubation with these drugs. On the contrary, p16-positive CERV196 showed increased susceptibility to sorafenib and sunitinib concerning suppression of AREG expression. Further studies are required to evaluate the HPV-dependent differences of therapy response and the possible consequences for treatment options.